Implantação da Instituição Escolar Pública em Ipiranga PR: a criação do Grupo Escolar Dr. Claudino dos Santos (1914) - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2020)
This dissertation has as its object of study the historical reconstruction of the Dr. Claudino dos Santos School Group, located in the city of Ipiranga-PR, being the result of research by the Graduate Program in Education Master and Doctorate, in the Policy Research Line and History of Education, from the State University of Ponta Grossa - PR. The Dr. Claudino dos Santos School Group was the first public school in the state, in Ipiranga - PR, and after a hundred years it remains the only state public school at the headquarters of this municipality. Specifically, it seeks to identify the historical context of the project to create school groups in republican Brazil, to understand the origin of the project to create school groups in Paraná and to analyze the city of Ipiranga and the creation of the Dr. Claudino dos Santos School Group, evidencing its determinants that influenced the public instruction of the State. Although the research has as object of study a single school group, this does not mean that analysis is isolated, since the capture of the historical context is interrelated and understood within an analysis of totality and interlocution with the other contexts. As for the methodological stance, the method to be used will be historical-dialectical materialism, which aims to understand the contradictions present in the dialectical movement of the research object. According to the epistemological basis used, the categories that permeated the research were, the contradiction, the totality and the ideology, through the bibliographic documentary research for the historical understanding of this centennial public school institution. The research has a documentary and bibliographic character. The time frame of the research covers the period from 1889 to 1914, taking into account, at the beginning of the period under study, the events of the end of the Empire, a period in which republican ideals are consolidating in Brazil, and thus the advent of the Proclamation of the Republic of the country, and one of the main education projects in this period, is the project for the creation of school groups, in Brazil it appeared in 1894, respectively in 1903 in Paraná, to be implanted in Ipiranga, in 1914, in the interior of Paraná. The dissertation is divided into three chapters: The creation of school groups in Brazil, the consolidation of the bourgeois class through education and its contradictions, the relations between the liberal ideals, the republican movement, politics in the transition period and the ideological clashes of large groups in the dispute for power in the Republic and, finally, the creation of school groups in Brazil. The second chapter entitled O Paraná Republicano ea Educação the republican movement in Paraná, the political relationship between the state and the farmers. The third chapter entitled the Republican Education Project in the city of Ipiranga - PR: the Dr. Claudino dos Santos School Group, addressed how the liberal principles of freedom, equality and secularity of the State were inserted in the Dr. Claudino dos Santos School Group, through educational reforms in the state of Paraná, the product of the economic context and political representation of the Ipiranga region in this period. The factors that conditioned educational reforms were contextualized, as well as the strong influence of Freemasonry and its positivist thinking in the public school in Ipiranga. This research becomes relevant, as it seeks to preserve school memory in the region, in addition to contributing to the production of knowledge in the area of History of Education, adding the research of the Research Group HISTEDBR- Campos Gerais.
Keywords: Criação do Grupo Escolar Dr. Claudino dos Santos; liberalismo; instituição escolar pública; Ipiranga-PR; Creation of the Dr. Claudino dos Santos School Group; liberalism; public school institution; Ipiranga-PR; CNPQ::CIENCIAS HUMANAS::EDUCACAO